Update on Bladder Cancer in Kano, Northern Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:A pilot study of 89 cases published 13 years ago (2003) revealed that bladder cancer was the second most common urologic malignancy in Kano with squamous carcinoma as the most frequent type (53%), with the peak prevalence in 5th/6thdecades and an overwhelming male preponderance (M:F = 5.2:1). This study endeavors to update on developments in bladder cancer profile since then.Materials and Methods:This was a 15-year (2001–2015) retrospective review of all histologically diagnosed bladder cancers at Aminu Kano Teaching Hospital, Kano.Results:Three hundred and twenty-seven bladder cancers were diagnosed during the study period. Peak age groups were the 5thand 6thdecades, with a mean of 51.2 years (±SD 11.74) and a male preponderance (7.6:1). Urothelial carcinoma was the most common histological type (49.6%), followed by squamous carcinoma (44.6%).Conclusion:Larger more representative sample size (327 cases) in this study compared to the earlier one (89 cases) 13 years ago largely accounted for the observed modest changes in histologic types, age, and sex distribution. Although the changes are modest, the general trend is towards that of the developed world – increasing urothelial carcinomas and increasing age profile.